2021
DOI: 10.1001/jamanetworkopen.2021.19812
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thrombosis With Hypereosinophilic Syndrome in Patients With Genetic Alterations

Abstract: IMPORTANCE Hypereosinophilic syndromes (HESs) are a rare group of disorders that result in overproduction of eosinophils, leading to tissue damage. Thrombotic complications in HES and associated risk factors in this patient population have not been extensively studied. OBJECTIVE To investigate the rates of and risk factors associated with thrombotic events in patients with HES, including markers of clonal hematopoiesis as evidenced by molecular aberrations on nextgeneration sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Additionally, in patients with idiopathic hypereosinophilic syndrome (a heterogeneous disorder characterized by proliferation of potentially neoplastic eosinophils), mutations in CHIP-associated genes indicate an increased risk for thrombotic events. 30 However, cardiovascular implications related to nondriver mutations have not been well characterized in the MPN population. In a small study of 16 patients with polycythemia vera, the presence of TET2 , DNMT3A , or ASXL1 mutations was associated with increased risk for thrombotic events.…”
Section: Influence Of Driver Mutations and Chip-associated Mutations ...mentioning
confidence: 99%
“…Additionally, in patients with idiopathic hypereosinophilic syndrome (a heterogeneous disorder characterized by proliferation of potentially neoplastic eosinophils), mutations in CHIP-associated genes indicate an increased risk for thrombotic events. 30 However, cardiovascular implications related to nondriver mutations have not been well characterized in the MPN population. In a small study of 16 patients with polycythemia vera, the presence of TET2 , DNMT3A , or ASXL1 mutations was associated with increased risk for thrombotic events.…”
Section: Influence Of Driver Mutations and Chip-associated Mutations ...mentioning
confidence: 99%
“…31,32 Additionally, rare inherited hypereosinophyllic syndromes have been associated with increased thrombotic risk. 33 Our study has many strengths, including the size of the cohort and the detailed CAD phenotyping by CTCA. However, there were some limitations.…”
Section: How Representative Are Our Findings To Global Cardiovascular...mentioning
confidence: 99%
“…Although the precise mechanism of eosinophil‐induced hypercoagulability is still unclear, contributing factors probably include initiation of the clotting cascade by expression of tissue factor, endothelial injury by major basic protein (MBP), stimulation of thrombus formation by binding to heparin and neutralizing its anticoagulating effects by eosinophilic cationic protein 7,8 . Data regarding the risk of thrombosis due to eosinophilia is limited to case reports and a small cohort study that showed that within a 29‐month follow‐up, 24% of the included patients, had one or more thrombotic events 9 . Antiphospholipid syndrome (APS) is associated with an increased risk of thrombosis which is medicated by impairment of fibrinolysis, reduction in protein C activity, procoagulant effects on platelets and endothelial cells, and induction of vascular endothelial growth factor (VEGF) 2,3,10 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Data regarding the risk of thrombosis due to eosinophilia is limited to case reports and a small cohort study that showed that within a 29-month follow-up, 24% of the included patients, had one or more thrombotic events. 9 Antiphospholipid syndrome (APS) is associated with an increased risk of thrombosis which is medicated by impairment of fibrinolysis, reduction in protein C activity, procoagulant effects on platelets and endothelial cells, and induction of vascular endothelial growth factor (VEGF). 2,3,10 Diagnosis of APS is done by revised Sapporo classification criteria which include clinical criteria (vascular thrombosis and pregnancy morbidity) and laboratory criteria: LA, aCL, and anti-β2 glycoprotein I antibodies.…”
Section: Case Presentationmentioning
confidence: 99%